The truth on Target II - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2018)
I use my "Viking Village" macroeconomic model for examining the economic meaning of the so-called Target-balances in the EMU. While some authors like H.W. Sinn and Thomas Mayer interpret them as liabilities that must be redeemed and paid interest on, others like Marcel Fratzscher, Martin Hellwig and the Bundesbank assess them as economically meaningless account entries only. While I myself tended to Sinn's view until recently, I have now changed my mind: According to the model results, neither Sinn nor his critics are right. In contrast, the economic meaning of Target balances depends critically on the rules on distributing seignorage in the EMU. In particular, under the existing rules, the Target balances are already burdened with interest implicitly, even without an explicit interest payment on them (which would indeed be inappropriate). On the other hand, because the common share of seignorage ends in case of a member country leaving the EMU, the Target balances would then immediately get relevant and must then be either redeemed or be paid explicit interest on. The counterargument that the interest rate is near to zero anyway is very weak, as the low interest policy itself creates huge redistributions that benefit the high indebted member states at the cost of the more solid ones. However, these redistributions are not directly related to the Target balances. Nevertheless, they should be paid more attention in the public.
Keywords: 330